2006
DOI: 10.1007/s00227-006-0367-4
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and evolution of the triplefin Tripterygion delaisi (Pisces, Blennioidei)

Abstract: The genus Tripterygion (Risso 1826) is restricted to the eastern Atlantic and the Mediterranean, and comprises only three species. T. melanuros and T. tripteronotus are essentially endemic to the Mediterranean, while Tripterygion delaisi occurs in the Atlantic and in the Mediterranean. Two subspecies of T. delaisi have been described (T. d. xanthosoma in the Mediterranean and T. d. delaisi in the Atlantic). Several scenarios have been proposed for the evolution of T. delaisi subspecies, but so far its subspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 39 publications
4
39
0
1
Order By: Relevance
“…Santos et al (1995a) suggested that such a decrease would have been enough to promote the local disappearance of warm water species such as P. parvicornis from the Azores. The less affected tropical western coast of Africa, the archipelago of Madeira, the westernmost Canary islands and some regions of the Mediterranean have been shown to act as refugia for species that were not able to survive the cold phases in the northern Atlantic locations (Domingues et al, , 2007a. Our findings support this hypothesis.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Santos et al (1995a) suggested that such a decrease would have been enough to promote the local disappearance of warm water species such as P. parvicornis from the Azores. The less affected tropical western coast of Africa, the archipelago of Madeira, the westernmost Canary islands and some regions of the Mediterranean have been shown to act as refugia for species that were not able to survive the cold phases in the northern Atlantic locations (Domingues et al, , 2007a. Our findings support this hypothesis.…”
Section: Discussionsupporting
confidence: 80%
“…Almada et al (2001) argued that the warmer water fish of the Atlanto-Mediterranean area survived in two distinct glacial refugia which acted as sources of post-glacial colonization: one in the west coast of Tropical/Subtropical Africa and Madeira, from which fish reached the Azores, and another inside the Mediterranean, from which the northeastern Atlantic waters adjacent to the Mediterranean entrance were colonized during the interglacials. These ideas have been supported by molecular studies on species like the pomacentrid Chromis limbata and the blenniid Tripterygion delaisi (Domingues et al, 2007a).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Distribution ranges of T. pavo and S. cretense reXect a clear preference for warm waters. Some warm water species such as Chromis chromis C. limbata and Tripterygion delaisi (Domingues et al 2006(Domingues et al , 2007, have been suggested to have survived the cold periods in warmer regions like Madeira, the tropical African coast and the southern Mediterranean, where the climatic conditions did not change signiWcantly during the Pleistocene (Thiede 1978;Crowley 1981). Indeed, Mediterranean populations of T. pavo and S. cretense show high levels of genetic diversity even in the eastern basin, pointing to an ancient colonization of this sea.…”
Section: Evolutionary History Of the Mediterranean And Adjacent Atlanticmentioning
confidence: 99%